(untitled) (Pedagogy of Higher and Secondary Education, 2021)
Topical problems of future maths teacher’s training under conditions of informatization of education have been investigated in the article. The thesus has presented the components of student’s professional preparesness to use information and communication technologies in heurustic teaching at Padagogical Universities. Some acceptances of forming a future teacher’s professional preparedness to use information and communication technologies in heuristic teaching of mathematicsare considered.